Engagement Law (Supreme Court Decision Number 951 K/Pdt/2015) - Setiawan, Ferdiansyah Prawira Negara; Mantiri, Juttah Christian (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
An agreement or contract is a legal relationship between two or more people who promise to give rise to legal consequences by means of an agreement. Legal consequences in the form of mutual rights and obligations between the parties. As a rule, an agreement or contract begins with a conflict or disagreement of interests between the parties, and the formation of a contractual relationship usually begins with a process of negotiation between the parties. This research method uses descriptive analysis. It is a method of using collected data to describe or provide an overview of the research subject and to present generally accepted conclusions. Based on the case in the Supreme Court decision No. 951 K/Pdt/2015 if Defendant I issues a statement that the "assets" a quo are no longer burdened with Mortgage Rights and then recommends to the Co-Defendant to Royalize the Plaintiff's "assets" a quo; the submission of Co-Defendant as a party in cassu solely to comply with the contents of the decision by ordering the Land Office of Makassar City to Roya the "asset" of the Plaintiff a quo and issue a Duplicate of HGB Certificate Number 477/Baru if the original certificate is lost by Defendant I. However, based on the opinion of the Defendant this is wrong and not right. Based on the legal facts found in the decision, the cassation petition from the Cassation Petitioners was rejected and the Cassation Petitioners were on the losing side, so the Cassation Petitioners were sentenced to pay court fees at this cassation level of Rp. 500,000.